'Жряху им, наричюще богы' ('They feel themselves the gods'): Sources of the content of ancient Russian pagan sanctuaries and their priests - M.N. Kozlov (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper is devoted to Eastern Slavonic pagan sanctuaries and their priests. This issue has been little studied by Russian researchers. The purpose of the investigation is historical reconstruction of the pagan cult system specifics of our ancestors in the pre-Christian age. The source analysis of the problem has been carried out. The biased criticism of the currently available basis for source studying of Ancient Rus during the pre-Mongolian period has been revealed. The following methods have been used to fulfill the above purpose: comparative philosophical religious and comparative analytical analysis, as well as such general scientific methods as analysis, synthesis, generalization, individualization, and historical narration. While working on the paper, both written and archaeological sources have been used. The written sources date back to the 6th – 17th centuries, including data on the cult system of the early Slavs in the pagan and early Christian epochs. They are native chronicles of the 11th – 14th centuries (Primary Chronicle, Hypatian Codex, and Novgorod First Chronicle), Lives of Saints, Legend of Yaroslavl Foundation. The materials of foreign authors of the 9th – 11th centuries (Ibn-Fadlan, Adam of Bremen) have been also considered. Archaeological data have been also carefully analyzed: materials of the excavation at East Slavonic settlements, sanctuaries, and warriors' mounds. Using the vast scope of historical data, the peculiarities of keeping small family sanctuaries, sanctuary settlements, city sacred centers and its priests have been reconstructed. The main peculiarities of pagan cult in cities have been discovered. The hierarchy of priests has been identified. Special attention has been paid to regular financing of a city sanctuary in the city of Kiev, when Vladimir, the Prince of Kiev, issued the corresponding order in 980.